Occurrence of glyphosate and AMPA in an agricultural watershed from the southeastern region of Argentina - Lupi, Leonardo; Miglioranza, Karina Silvia Beatriz; Aparicio, Virginia Carolina; Marino, Damian Jose Gabriel; Bedmar, Francisco; Wunderlin, Daniel Alberto (Elsevier, 2018)
Glyphosate (GLY) and AMPA concentrations were determined in sandy soil profiles, during pre- and post-application events in two agricultural soybean fields (S1 and S2). Streamwater and sediment samples were also analyzed. Post-application sampling was carried out one month later from the event. Concentrations of GLY + AMPA in surface soils (0–5 cm depth) during pre-application period showed values 20-fold higher (0.093–0.163 μg/g d.w.) than control area (0.005 μg/g d.w.). After application event soils showed markedly higher pesticide concentrations. A predominance of AMPA (80%) was observed in S1 (early application), while 34% in S2 for surface soils. GLY + AMPA concentrations decreased with depth and correlated strongly with organic carbon (r between 0.74 and 0.88, p < 0.05) and pH (r between − 0.81 and − 0.76, p < 0.001). The slight enrichment of pesticides observed from 25 cm depth to deeper layer, in addition to the alkaline pH along the profile, is of high concern about groundwater contamination. Sediments from pre-application period showed relatively lower pesticide levels (0.0053–0.0263 μg/g d.w.) than surface soil with a predominance of glyphosate, indicating a limited degradation. Levels of contaminants (mainly AMPA) in streamwater (ND-0.5 ng/mL) denote the low persistence of these compounds. However, a direct relationship in AMPA concentration was observed between sediment and streamwater. Despite the known relatively short half-life of glyphosate in soils, GLY + AMPA occurrence is registered in almost all matrices at different sampling times (pre- and post-application events). The physicochemical characteristics (organic carbon, texture, pH) and structure of soils and sediment in addition to the time elapsed from application determined the behavior of these contaminants in the environment. As a whole, the results warn us about vertical transport trough soil profile with the possibility of reaching groundwater.